Dietary fatty acids improve perceived sleep quality, stress, and health in migraine: a secondary analysis of a randomized controlled trial - Faurot, Keturah R.; Park, Jinyoung; Miller, Vanessa; Honvoh, Gilson; Domeniciello, Anthony; Mann, J. Douglas; Gaylord, Susan A.; Lynch, Chanee E.; Palsson, Olafur; Ramsden, Christopher E.; MacIntosh, Beth A.; Horowitz, Mark; et al. (Frontiers in Pain Research, 2023)
Background: Migraine is a prevalent disabling condition often associated with comorbid physical and psychological symptoms that contribute to impaired quality of life and disability. Studies suggest that increasing dietary omega-3 fatty acid is associated with headache reduction, but less is known about the effects on quality of life in migraine.Methods: After a 4-week run-in, 182 adults with 5-20 migraine days per month were randomized to one of the 3 arms for sixteen weeks. Dietary arms included: H3L6 (a high omega-3, low omega-6 diet), H3 (a high omega-3, an average omega-6 diet), or a control diet (average intakes of omega-3 and omega-6 fatty acids). Prespecified secondary included daily diary measures (stress perception, sleep quality, and perceived health), Patient-Reported Outcome Measurement Information System Version 1.0 ([PROMIS©) measures and the Migraine Disability Assessment (MIDAS). Analyses used linear mixed effects models to control for repeated measures.The H3L6 diet was associated with significant improvements in stress perception (adjusted mean difference (aMD): -1.5 [95% confidence interval: -1.7–1.2]), sleep quality (aMD: 0.2 [95% CI:0.1-0.2]), and perceived health (aMD: 0.2 [0.2-0.3]) compared to the control. Similarly, the H3 diet was associated with significant improvements in stress perception (aMD: -0.